CHARACTERIZATION OF METEOROLOGICAL DROUGHT USING RAINFALL DEFICIT INDEX FOR EFFECTIVE CROP PRODUCTION IN YOLA SOUTH LGA, ADAMAWA STATE NIGERIA - AA, SADIQ (Innovare Journal of Agricultural Sciences, 2022)
The study aimed at characterization of meteorological drought using rainfall deficit index (RDI) for effective Crop Production in Yola South LGA, Adamawa State Nigeria. Rainfall data for the period of 50 years (1969–2018) were analyzed using RDI. The results revealed that the month of March, April, May, June, and October were characterized as severe drought episodes with <26% of mean rainfall in 34–50 years of the study period. The month of July experienced severe drought in 21 years and 16 years (33%) in September. August was characterized with normal rainfall in 17 years (34%) and no drought episodes occurred in 16 years (32%), respectively. The annual drought characterization shows that 39 years (78%) were classified with no drought where only 10% (5 years) were quantified as severe drought which mostly occurred in the first (1969–1978) and fourth (1999–2008) decades under the study. To realize effective crop production, farmers are, therefore, recommended to adjust the planting dates and also to adopt the use of early maturing crop varieties with low water use efficiency in the area.